A Marketing Analysis of the Equitability of Water/Sewage Service Improvements. Issue 4 (1st April 2015) - Hecht, Jonathan; Reid, Scott; Chalak, Ali
Abstract : Advances in choice modeling allow for the approximation of the spread of preferences within a population and the estimation of individual‐level preferences. These techniques translate preference estimates into information that is more useful from a managerial perspective. This study illustrates the application of such techniques to stated preference data collected for a water and sewage utility in the United Kingdom. Using a choice experiment, customers' willingness to pay for various water and sewage service improvements was estimated. Results showed a substantial willingness to pay for various private‐good services (such as water and sewage services) and public‐good environmental services (such as reduced greenhouse gas emissions). The customer population was segmented according to customer preferences, allowing for a description of the characteristics of each segment. Potential customer demand was forecasted for different packages of service improvements offered to customers at varying prices. The analysis thus addressed issues of customer acceptability and equity relating to the provision of service improvements.